ANALYSIS OF WARFIGHTING FUNCTIONS– THE UKRAINIAN COUNTEROFFENSIVE IN CONTEXT (Security Dialogues, 2024)
This paper provides a detailed analysis ofwarfighting functions during the counteroffensive of the Ukrainian forces against Russian forces, as well as the efficiencyof warfightingfunctions, which has a significant impact on the results of the war. It will cover the periodfrom the start of the counter-offensive of the Ukrainian forces, from June 2023, when somevictories were recorded by the Ukrainian forces.Through the analysis and processing of confidential and already available information fromsocial networks, media and the Washington Post, and in accordance with the comparisonwith the US doctrine, a special emphasis was placed on one of the warfighting functions inUkrainian counter-offensive, that is, the system for combat service support.The method ofanalyses and synthesis was used to summarize the results and arrive at the conclusion.Hence it is confirmed that in terms of the organization and implementation of the combatservice support warfighting function, the Ukrainian forces have failed to meet the rightrequirements in the right place and at the right time. The main culprit in all of this is the lackof sufficient time for preparation and training of personnel for different models of the sametype of assets that were donated by Western countries during the war, as well as the rejectionof US military officials’ advice to use frontal attack along one axis.